Bioactive chemical constituents from the seed testa of Vernicia fordii as potential neuroinflammatory inhibitors. (March 2020) - Chen, Gang; Zhao, Weihong; Li, Yang; Zhou, Di; Ding, Jing; Lin, Bin; Li, Wei; Yang, Yanqiu; Liu, Jingyu; Hou, Yue; Li, Ning
Abstract: Eight previously undescribed and 15 known components, including six neolignans, two monolignan, three sesquineolignans, three dineolignans, eight phenylpropanoids, and one steroid were identified from the seed testa of Vernicia fordii . Their structures were established based on the comprehensive analysis of NMR and ECD data. The anti-neuroinflammatory effects of the isolates were evaluated through nitrite assays in LPS-induced BV2 cells. As a result, isodiverniciasin A, diverniciasin B, diverniciasin C, isoprincepin, princepin, 3, 3′-bisdemethylpinoresinol, (+)-7-epi-sesamin-dicatechol, isoamericanin A, americanin B, 7 S, 8 R -americanin D, 4-hydroxyl cinnamic aldehyde, 3-hydroxyl-4-methoxyl cinnamic aldehyde and 24 R -6 β -hydroxy-24- ethylcholest-4-en-3-one exhibited significant inhibitory effects on nitric oxide (NO) production and isoprincepin, princepin, americanin B, and 4-hydroxyl cinnamic aldehyde suppressed the overexpression of inflammatory cytokines TNF-α, IL-1β, and IL-6 in over-activated microglia. The results suggested that bioactive ingredients from the seed testa of V. fordii can serve as potential therapeutic agents for neurodegenerative diseases. Graphical abstract: Twenty-three components, including eight undescribed ones, were identified from the seed testa of Vernicia fordii (Hemsl.) Airy Shaw (Euphorbiaceae). Some of the isolates showed anti-neuroinflammatory effects in activated microglia cells. Image 1 Highlights: Eight previously undescribed and fifteen known compounds were isolated from Vernicia fordii . Twenty three compounds from Vernicia fordii showed inhibitory effects on nitric oxide production in over-activated microglial. A plausible biosynthetic pathway was proposed.